Image-guided interventional radiological delivery of chimeric antigen receptor (CAR) T cells for pleural malignancies in a phase I/II clinical trial. (March 2022) - Ghosn, Mario; Cheema, Waseem; Zhu, Amy; Livschitz, Jennifer; Maybody, Majid; Boas, Franz E.; Santos, Ernesto; Kim, DaeHee; Beattie, Jason A.; Offin, Michael; Rusch, Valerie W.; Zauderer, Marjorie G.; et al.
Highlights: CAR T cells administered intrapleurally in 31 participants with pleural cancers. Intrapleural delivery of CAR T cells using intracavitary/intratumoral routes is safe. Repeated administration of therapeutic agents to the pleural cavity is feasible. Abstract: Objectives: We describe techniques and results of image-guided delivery of mesothelin-targeted chimeric antigen receptor (CAR) T cells in patients with pleural malignancies in a phase I/II trial (ClinicalTrials.gov: NCT02414269). Materials and methods: Patients without a pleural catheter or who lack effusion for insertion of a catheter (31 of 41) were administered intrapleural CAR T cells by interventional radiologists under image guidance by computed tomography or ultrasound. CAR T cells were administered through a needle in an accessible pleural loculation (intracavitary) or following an induced loculated artificial pneumothorax. In patients where intracavitary infusion was not feasible, CAR T cells were injected via percutaneous approach either surrounding and/or in the pleural nodule/thickening (intratumoral). Pre- and post-procedural clinical, laboratory, and imaging findings were assessed. Results: CAR T cells were administered intrapleurally in 31 patients (33 procedures, 2 patients were administered a second dose) with successful delivery of planned dose (10–186 mL); 14/33 (42%) intracavitary and 19/33 (58%) intratumoral. All procedures were completed within 2 h of T-cell thawing. There were no procedure-related adverse events greater than grade 1 (1 in 3 patients had prior ipsilateral pleural fusion procedures). The most common imaging finding was ground glass opacities with interlobular septal thickening and/or consolidation, observed in 12/33 (36%) procedures. There was no difference in the incidence of fever, CRP, IL-6, and peak vector copy number in the peripheral blood between infusion methods. Conclusion: Image-guided intrapleural delivery of CAR T cells using intracavitary or intratumoral routes is feasible, repeatable and safe across anatomically variable pleural cancers.